Exercise-Based Physiotherapy Intervention for Optimizing Motor Function and Lung Capacity in Elderly Patients with Physical Weakness and Cardiovascular Dysfunction: A Case Study - Arief, Hendrawan; Setiyawati, Dwi; Sohimah (SAINS INDONESIANA, 2025)
Background:Older adults with physical frailty and cardiovascular dysfunction are at high risk of decreased mobility and pulmonary capacity, leading to reduced independence and quality of life. A multicomponent physiotherapy exercise program may optimize both functions. Objective: To evaluate the effects of a multicomponent physiotherapy intervention on mobility and pulmonary capacity in an older adult with physical frailty and cardiovascular dysfunction. Methods: A single-subject research design (A-B-A) was conducted on a 70-year-old female patient diagnosed as frail with a history of hypertension. The 6-week intervention included resistance training, aerobic exercise, balance training, and breathing exercises. Outcomes measured were Six-Minute Walk Test (6MWT), 30-Second Chair Stand Test, Timed Up and Go (TUG), Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV₁), Maximal Inspiratory Pressure (MIP), and Borg Dyspnea Scale. Results: After intervention, the 6MWT distance increased by 33.3%, lower limb strength by 50%, TUG time decreased by 23.9%, FVC increased by 13.5%, FEV₁ by 12.0%, MIP by 23.6%, and Borg Dyspnea Scale score decreased by 40%. Most improvements were retained during follow-up. Conclusion: A multicomponent physiotherapy program was effective in improving mobility and pulmonary capacity in an older adult with physical frailty and cardiovascular dysfunction, and was safe for clinical application.